Scrub typhus complicating hemophagocytic lymphohistiocytosis: a case report. - Kartik Goel; Reshma Prakash; Harsh Kansagara; Shailesh Kumar; Rupesh Yadav (Critical Care Innovations)
Hemophagocytic lymphohistiocytosis (HLH) is a rare disorder characterised by uncontrolled activation of CD8+ T lymphocytes and macrophages, resulting in organ damage. While primary HLH is associated with genetic defects, secondary HLH can be triggered by infections, malignancies, or autoimmune disorders. Scrub typhus-induced HLH underscores the importance of considering tropical fevers as potential triggers for HLH. We present the case of a 27- year-old man who was admitted with no known comorbidities, who had multiple complaints of loose stool for the past 10 days,, fever for the past 8 days and dry cough for the past 3 days. The initial investigation showed bicytopenia, transaminitis, and hyponatremia. A tropical fever study was done, which was negative for typhoid fever, dengue, malaria, HIV, and viral hepatitis. Scrub IgM turned out to be positive. EBV IgM was negative, and Leptospira IgM was negative. The patient was treated with IV antibiotic doxycycline. Since the patient's counts did not improve and had a daily fever spike despite being on antibiotic. On the basis of the H score, the probability of HLH came out. Due to high suspicion of HLH, pulse steroids (1 g of methylprednisolone for 3 days) were started and monitored for counts and fever spikes, which settled after the course of steroids. At follow-up, the patient had no episodes of fever, and the bicytopenia resolved. Early recognition and intervention are crucial for reducing mortality in HLH. This case report contributes to pathophysiology, diagnosis and management the understanding of HLH, highlighting the need for vigilance in patients presenting with scrub typhus and associated complications.